The Sixteenth Mississippi Infantry : Civil War Letters and Reminiscences - Evans, Robert G., 1949- (Book collections on Project MUSE., 2002)
They fought in the Shenandoah campaign that blazed Stonewall Jackson's reputation. They fought in the Seven Days' Battles and at Antietam, Fredericksburg, Chancellorsville, and Gettysburg, in the Wilderness campaign, and at Spotsylvania. At the surrender they were beside General Robert E. Lee in Appomattox. From the beginning of the war to its very end the men of the Sixteenth Mississippi endured. In this collection of their letters and their memories, both historians and Civil War buffs will find the fascinating words of these common soldiers in one of the most notable units in the Army of No.